The role of Gel‐Ppy‐modified nerve conduit on the repair of sciatic nerve defect in rat model. Issue 5 (13th April 2023) - Jiang, Liangfu; Ouyang, Xingyu; Zhang, Dupiao; Wang, Gang; Zhang, Zhe; Wang, Wei; Yan, Hede
Abstract: The serious clinical challenge of peripheral nerve injury (PNI) is nerve regeneration. Nerve conduit represents a promising strategy to contribute to nerve regeneration by bridging injured nerve gaps. However, due to a unique microenvironment of nerve tissue, autologous nerves have not been substituted by nerve conduit. Nerve regeneration after nerve conduit implantation depends on many factors, such as conductivity and biocompatibility. Therefore, Gelatin (Gel) with biocompatibility and polypyrrole (Ppy) with conductivity is highly concerned. In this paper, Gel‐Ppy modified nerve conduit was fabricated with great biocompatibility and conductivity to evaluate its properties of enhancing nerve regeneration in vivo and in vitro. The proliferation of Schwann cells on Gel‐Ppy modified nerve conduit was remarkably increased. Consistent with in vitro results, the Gel‐Ppy nerve conduit could contribute to the regeneration of Schwann cell in vivo. The axon diameters and myelin sheath thickness were also enhanced, resulting in the amelioration of muscle atrophy, nerve conduction, and motor function recovery. To explain this interesting phenomenon, western blot results indicated that the Gel‐Ppy conduit facilitated nerve regeneration via upregulating the Rap1 pathway to induce neurite outgrowth. Therefore, the above results demonstrated that Gel‐Ppy modified nerve conduit could provide an acceptable microenvironment for nerve regeneration and be popularized as a novel therapeutic strategy of PNI. Abstract : We achieved drug loading by grafting Gel and Ppy, followed by blending electrospinning with PLLA. The synthesized material was then wrapped around the sciatic nerve of rats after surgery for the treatment of sciatic nerve injury.